Review Article about Radioactive Contamination - Ghulam, Zainab Faisal; Dali, Mahmoud Ahmed; Hamid, Mahmoud Majeed (American Journal of Biomedicine and Pharmacy, 2024)
Radioactive pollution is the increase in natural radiation levels due to human activities. Human activities that can release radiation include activities involving radioactive materials such as mining, handling and processing of radioactive materials, handling and storage of radioactive waste, as well as the use of radioactive reactions to generate energy (nuclear power plants), Radioactive pollution occurs when radioactive elements are present in the atmosphere or environment, especially when their presence is unexpected and creates an environmental threat due to radioactive decay. In addition to the use of radiation in medicine (such as X-rays) and research. Radiation is basically of two types: 1. Non-ionizing radiation: These are electromagnetic waves with a wavelength longer than near-ultraviolet to radio waves. These do not contain enough energy to ionize them. 2. Ionizing radiation: These are electromagnetic radiations with high energy, such as short-wavelength ultraviolet, X-rays, and gamma rays. Energetic radiation produced by radioactive decay can cause the atoms and molecules of the medium through which they pass to ionize and convert them into charged ions. The radiations are (γ) gamma, (β) beta, (α) alpha produced by a process called radioactive decay. They can also affect other non-radioactive atoms to become radioactive and emit radioactive radiation. Sources of radiation contamination Nuclear power plants. Mining for nuclear fuel, nuclear waste, nuclear power plant accidents, nuclear testing, diagnostics, biological research and nuclear weapons are all potential sources of radioactive contamination. On average, 82% of this radiation comes from natural sources and 18% from anthropogenic sources (i.e. those associated with human activities). The main natural source of radiation is radon gas, which accounts for about 55% of the total radiation dose. The main anthropogenic sources of radiation are medical X-rays and nuclear medicine.